JavaScript shen ru jing yao = JavaScript enlightenment / = JavaScript enlightenment - Lindley, Cody 1976- (GoTop Information, Inc., 2013)
Detailed summary in vernacular field.
Includes index
Keywords: JavaScript (Computer program language); JavaScript (Langage de programmation)